Mucosal Involvement in Bullous Pemphigoid Is Mostly Associated with Disease Severity and to Absence of Anti-BP230 Autoantibody - Clapé, Ariane; Muller, Céline; Gatouillat, Grégory; Le Jan, Sébastien; Barbe, Coralie; Pham, Bach-Nga; Antonicelli, Frank; Bernard, Philippe (Frontiers in Immunology, 2018)
Bullous pemphigoid (BP) is the most common autoimmune bullous disease and typically affects the elderly. Binding of specific autoantibodies to BP180/230 hemidesmosomal components induces an inflammatory response leading to skin blister formation. Unusual manifestations of BP include additional mucous membrane involvement, without pathophysiological knowledge associated to the formation of these lesions. We here performed a prospective study on series of consecutive BP patients with (n = 77) and without (n = 18) mucosal involvements at baseline to further investigate why some BP patients display mucosal lesion and other not. Analysis of disease activity showed that BP patients with mucosal involvement displayed a higher total BPDAI score (P = 0.008), but also higher skin and blister/erosion BPDAI scores (P = 0.02 and P = 0.001, respectively). In contrast, the erythema/urticaria BPDAI score was identical between the two groups of patients. The erythema/urticaria BPDAI score, but not the blister/erosion BPDAI score, was correlated with the serum concentration of anti-BP180 NC16A autoantibodies in patients with mucosal involvement. In multivariate analysis, the absence of anti-BP230 autoantibody was the only factor independently associated with mucosal involvement [OR 7.8; 95% CI, 3.1 – 19.6] (P< 0.0001). Analysis of the distribution of BP patients according to BPDAI scores revealed a shift towards higher blister/erosion BPDAI scores for BP patients with mucosal involvement. This study indicates that mucosal lesions are clinically mainly related to disease severity and immunologically to the absence of anti-BP230 antibodies.